Brazilian healthcare model for people with mental disorders: a systematic literature review - Marcelo Theophilo Lima; Fernanda Maria Duarte Nogueira (Universidade de Fortaleza, 2013)
Objective: To evaluate the process of implementing the Brazilian psychiatric reform, especially regarding its impact on families' management of healthcare issues. Methods: Interpretative research performed between August 2011 and January 2012, where symbolic interactionism was used as theoretical reference and Grounded Theory was used as the methodological reference. Initially, 49 articles on the subject were selected applying as descriptors mental health, psychiatric reform and psychosocial care, in Scielo, lIlACS and university libraries' databases. of these, 17 articles were excluded for being published prior to 2008 and 18 for having approaches not comprised in the scope of the study. Results: The power relationships in the treatment method were identified as causal conditions of the de-hospitalization process, which occurs in a context of deficiency in the network intended to replace psychiatric hospitals, therefore requiring the participation of patients' families in their reintegration at home and treatment. This strategy to deconstruct the psychiatric hospital-based model results in an excessive burden to the families. Conclusion: If, on one hand, the shift from hospitalization to in-home care, with embracement of the disease and of patients' suffering in their very social relationships, was to propose the recovery of patients' civil and human rights and their remaining into the society, on the other hand, it creates another series of problems, such as the emotional and logistical burden imposed on patients' families.